2018
DOI: 10.1038/s41388-018-0294-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of stromal Dickkopf-3 in prostate cancer: opposing roles for TGFBI and ECM-1

Abstract: Aberrant transforming growth factor–β (TGF-β) signaling is a hallmark of the stromal microenvironment in cancer. Dickkopf-3 (Dkk-3), shown to inhibit TGF-β signaling, is downregulated in prostate cancer and upregulated in the stroma in benign prostatic hyperplasia, but the function of stromal Dkk-3 is unclear. Here we show that DKK3 silencing in WPMY-1 prostate stromal cells increases TGF-β signaling activity and that stromal cell-conditioned media inhibit prostate cancer cell invasion in a Dkk-3-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 53 publications
(93 reference statements)
2
53
0
1
Order By: Relevance
“…However, DKK3 is the most structurally divergent member of the Dickkopf family (Krupnik et al, 1999) and has varied effects on Wnt, ranging from no effect (Krupnik et al, 1999;Pinho Christof Niehrs, 2007;Romero et al, 2013) to promoting (Ferrari et al, 2019;Nakamura and Hackam, 2010;Yin et al, 2018) or inhibiting Wnt (Bhattacharyya et al, 2017;Leonard et al, 2017;Liu et al, 2019;Sharma Das et al, 2013). DKK3 also functions as both a positive and negative regulator of TGFβ signaling, depending on the model (Al Shareef et al, 2018;Busceti et al, 2017;Kardooni et al, 2018;Li et al, 2017;Pinho Christof Niehrs, 2007;Romero et al, 2013;Wang Z et al, 2015), but DKK3 did not impact TGFβ in this study (data not shown). Despite conflicting reports of DKK3's signaling targets, it has consistently been shown to restrain cell proliferation (Kawano et al, 2006;Leonard et al, 2017).…”
Section: 25d Regulates Dkk3 In Lineage-committed Cellsmentioning
confidence: 65%
See 1 more Smart Citation
“…However, DKK3 is the most structurally divergent member of the Dickkopf family (Krupnik et al, 1999) and has varied effects on Wnt, ranging from no effect (Krupnik et al, 1999;Pinho Christof Niehrs, 2007;Romero et al, 2013) to promoting (Ferrari et al, 2019;Nakamura and Hackam, 2010;Yin et al, 2018) or inhibiting Wnt (Bhattacharyya et al, 2017;Leonard et al, 2017;Liu et al, 2019;Sharma Das et al, 2013). DKK3 also functions as both a positive and negative regulator of TGFβ signaling, depending on the model (Al Shareef et al, 2018;Busceti et al, 2017;Kardooni et al, 2018;Li et al, 2017;Pinho Christof Niehrs, 2007;Romero et al, 2013;Wang Z et al, 2015), but DKK3 did not impact TGFβ in this study (data not shown). Despite conflicting reports of DKK3's signaling targets, it has consistently been shown to restrain cell proliferation (Kawano et al, 2006;Leonard et al, 2017).…”
Section: 25d Regulates Dkk3 In Lineage-committed Cellsmentioning
confidence: 65%
“…We observed that DKK3 was not expressed by the stem cells in organoids, similar to patient tissue (Henry et al, 2018), indicating that DKK3 acts downstream to regulate cell growth ( Figure 5E). Notably, DKK3 is also highly expressed in the stroma of the prostate, which indicates a multifaceted role for this protein that can be explored in the future using co-culture models (Al Shareef et al, 2018;Henry et al, 2018;Zenzmaier et al, 2013). The increase in organoid size induced by 1,25D may seem contradictory to the traditional anti-proliferative role of Vitamin D metabolites (Feldman et al, 2014;Murphy et al, 2017;Wagner et al, 2013).…”
Section: 25d Regulates Dkk3 In Lineage-committed Cellsmentioning
confidence: 99%
“…Also in the current study, measurement of SOST and DKK-1 remains a major challenge. Current literature reports that pro-inflammatory markers, including IL-1β, TNFα and TGFβ (Loots et al, 2012;Weng et al, 2012;Korkosz et al, 2014;Sebastian and Loots, 2017;Al Shareef et al, 2018), can increase Sost and Dkk-1 in bone and cartilage by transcriptional control. This finding could not be reproduced in our study with DPC.…”
Section: Discussionmentioning
confidence: 99%
“…In human DPC, the hypoxia mimetic agent L-mimosine (L-MIM) downregulated SOST and hypoxia downregulated DKK-1 mRNA production, but this effect could not be reproduced at protein levels, where SOST and DKK-1 were only produced marginally or not at all (Janjić et al, 2018a). Interleukin (IL)-1 (Weng et al, 2012;Ruscitti et al, 2015), tumor necrosis factor (TNF)α (Korkosz et al, 2014;Sebastian and Loots, 2017) and transforming growth factor (TGF)β (Loots et al, 2012;Al Shareef et al, 2018), markers of inflammation, are able to increase levels of Sost and Dkk-1.…”
Section: Introductionmentioning
confidence: 99%
“…Exosome-mediated transfer of miR-92a from colon cancer cells to endothelial cells leads to angiogenesis induction through downregulation of Dickkopf-3 (DKK3) and claudin-11 [36]. Several studies have shown that DKK3 has a diverse function in tumor angiogenesis and oncogenesis [103][104][105][106]. Busceti et al have indicated an angio-promoting role of DKK3 via VEGF upregulation [107].…”
Section: Pro-angiogenic Mirnas In Crcmentioning
confidence: 99%